Philosophical writings - Herder, Johann Gottfried, 1744-1803 (Cambridge texts in the history of philosophy., 2002)
Johann Gottfried von Herder (1744-1803) is one of the most important German philosophers of the eighteenth century, who had enormous influence on later thinkers such as Hegel, Schleiermacher, and Nietzsche. His wide-ranging ideas were formative in the development of linguistics, hermeneutics, anthropology, and bible scholarship, and even today they retain their vitality and relevance to an extraordinary degree. This volume presents a new translation by Michael Forster of Herder's most important and characteristic philosophical writings (some of which have never before been translated) in his areas of central interest, including philosophy of language, philosophy of mind, philosophy of history, and political philosophy, as well as his general philosophical program. An introduction sets the writings in their historical context and examines their philosophical achievement.